Design, Docking, Insilco ADME Prediction Of Novel Indole Based Benzamide Scaffolds Targeting For Estrogen Receptor Alfa In Af-2 Domain For Effective Anticancer Treatment (Journal of Pharmaceutical Negative Results, 2022)
Aim: To discover some novel indole based benzamide scaffold and their screening through in silico approach.Background: Designed 7-substituted -1-(4-(piperidine-1-yl methoxy)benzyl)-1H-indole-3-carboxamide derivatives targeting on ERα modulators, several interactions between the ligand and amino acid residues that would probably elicit fruitful modulation of the receptor using 4XI3 pdb of ERα.Objective: Studied in silico novel molecules of 7-substituted -1-(4-(piperidine-1-yl methoxy)benzyl)-1H-indole-3-carboxamide derivatives and test their abilities to modulate ER-α through human cell line cultures as anti-breast cancer agent.Method: Designed novel 7-substituted -1-(4-(piperidine-1-yl methoxy) benzyl)-1H-indole-3-carboxamide derivatives and in silico method involved to study their virtual screening for the receptor modulation by molecular docking studies using Auto-dock Vina in PyRx. To determine the binding interactions for best-fit conformations in AF-2 binding site of the ERα receptor studied using Discovery studio visualizer (DSV) and ADME predictions by Swiss ADMET.Result : The result based on the docking studies, The designed ligands B73bi, B73axiv B73bvi ,B73av, B73avi, B73avi, B73axiv, B74ai B74ai and B74bxiv have shown better Binding Affinity than rest, as compare with the standard drug Bazedoxifene (Baz). The observed result explained the presence of substitution at 7th position of the benzamide on indole scaffold containing alkyl, ester, amide, N,N diamine groups shows promising interactions like BZD. Therefore, B73aiii carrying halide (G Score= -10.3), B73av carrying methoxy benzoate (G Score = -9.9), B73axiv carrying ethoxy (G Score= -9.4) were found to interact suitably with the active amino acid residues in the targeted cavity where reported interaction with the standard to be involved.Conclusion: The most promising substituted benzamide analogue on indole can be synthesized and evaluated to verify the ani-cancer activity for breast cancer.